Unveiling Power: A Van Dijk Discourse Analysis of Prabowo's Presidential Inauguration Speech - Sutarman, Sutarman; Saputra, Ari; Abdussamad, Zainudin (Lembaga Yasin AlSys, 2024)
This study examines Prabowo Subianto's presidential inauguration speech through the lens of Teun A. van Dijk's Discourse Analysis approach. Utilizing Van Dijk's framework, which emphasizes the social and cognitive dimensions of language, the analysis explores how Prabowo constructs his image, communicates key political messages, and seeks to influence public opinion during the inaugural address. By examining the linguistic features, rhetorical strategies, and underlying ideologies present in the speech, this research uncovers the ways in which Prabowo uses discourse to shape perceptions of his leadership, promote national unity, and frame political issues. The findings reveal how the speech serves as an important tool for Prabowo to communicate his vision of Indonesia and to persuade the audience of his political agenda. This study contributes to a better understanding of the role of language in political discourse and highlights the power of discourse analysis in uncovering the nuanced interplay between language, power, and politics.